Artificial Intelligence in Public Service and Governance in Nigeria - Chibuzo Charles Nwosu; Dike Chijioke Obalum; Mathias Ozoemena Ananti (Goodwood Publishing, 2024)
Purpose: This study explores the current state of Artificial Intelligence (AI) implementation in Nigeria’s public service and examines its potential benefits, challenges, and strategic pathways for improving governance and service delivery. Methods: This study employed a qualitative research design using secondary data collected from academic articles, books, policy documents, and reports related to AI and governance. A thematic analysis and content analysis approach were applied to identify key issues, experiences, and perspectives concerning AI adoption in public services. Results: The findings indicate that AI adoption in Nigeria’s public sector remains at an early stage, with emerging applications in e-governance, healthcare, banking, real estate, and security services. Major barriers include inadequate infrastructure, limited digital literacy, insufficient human capital, and weak public awareness of AI. Conclusions: AI has significant potential to improve efficiency, transparency, accessibility, and responsiveness in Nigeria’s public governance and service delivery systems. Limitations: This study is limited to secondary data analysis and does not include empirical field data from public institutions in Nigeria. Contributions: This study provides a comprehensive understanding of how AI can be adopted in Nigeria’s unique environment. Novelty: The novelty of this study lies in its examination of Nigeria’s unique challenges in adopting artificial intelligence for public governance, particularly infrastructure limitations, data privacy concerns, workforce readiness, and the need for supportive regulatory frameworks.